Danny Duncan's Play "Billie's Song" Performed in San Francisco - Watkins, Howard::::::::: (1984)
Nina Causey (black and white suit), Andre McQueen, ?, Ricky Le Blanc, ?, ?, Carmelita Herron, Ken Kingsbury